The exploration and practice of curriculum ideological and political education into the whole process of molecular diagnostics teaching - Chen, Hao; LIU Tangyuheng; ZHOU Wenjing; JIAO Lin; ZHOU Juan (Pacific International Journal, 2024)
Molecular diagnostics, as one of the core courses of medical laboratory technology major, has dual attributes of natural science and humanities. Combined with the social background of the post-epidemic era, by analyzing the necessity of implementing curriculum ideological and political education, it explores the whole-course education, all-round education and full education from the aspects of teaching design and methods, and provides new ideas for the realization of accurate ideological and political education.